NUTRIENT CONCENTRATION AND PH IN THE CISADANE ESTUARINE AND COASTAL WATERS - Muchtar, Muswerry (Marine Research in Indonesia, 2007)
The study on the fluctuation of dissolved nutrient concentrations and acidity (pH) in the Cisadane Estuary was carried out in May 2004 October 2004 and July 2005. Inorganic phosphate, nitrate and silicate of the surface water were analyzed, using Spectrophotometer and pH was measured with a pH meter. Generally the nutrient concentrations in the estuary were higher compared to those in the coastal and offshore areas. The concentrations were gradually becoming lower and lower toward the open sea. Their fluctuation depended not only on the environmental condition but also on the water volurrie from the land and the mangrove forest in that area.